2022
DOI: 10.3390/pharmaceutics14020395
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin-Type Drugs in Tumor Cell Death: Mechanisms, Combination Treatment with Biologics and Nanoparticle Delivery

Abstract: Artemisinin, the most famous anti-malaria drug initially extracted from Artemisia annua L., also exhibits anti-tumor properties in vivo and in vitro. To improve its solubility and bioavailability, multiple derivatives have been synthesized. However, to reveal the anti-tumor mechanism and improve the efficacy of these artemisinin-type drugs, studies have been conducted in recent years. In this review, we first provide an overview of the effect of artemisinin-type drugs on the regulated cell death pathways, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 212 publications
(212 reference statements)
0
6
0
Order By: Relevance
“…Beyond its direct antiparasitic properties, AS may have additional therapeutic benefits due to its capacity to regulate the expression of apoptotic proteins Bax, Beclin, and Caspase activity through the destruction of contaminated cells, stop the infection from spreading, and encourage tissue regeneration ( 40 ). Recently, documented studies on 56 phytochemicals including AS showed significant reduction in TNF-α, IL2, CD44, and IFN-γ via NF-kB pathways in vitro and in vivo models ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond its direct antiparasitic properties, AS may have additional therapeutic benefits due to its capacity to regulate the expression of apoptotic proteins Bax, Beclin, and Caspase activity through the destruction of contaminated cells, stop the infection from spreading, and encourage tissue regeneration ( 40 ). Recently, documented studies on 56 phytochemicals including AS showed significant reduction in TNF-α, IL2, CD44, and IFN-γ via NF-kB pathways in vitro and in vivo models ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo studies have reported that ART has antitumor, antifungal, anti-malarial, and anti-ulcer efficacy [ 204 ]. However, ART has a lower solubility in water, a shorter half-life and an increased first-passage metabolism, which limits its therapeutic efficacy [ 205 ]. The synthesis of ART-containing NPs improve the pharmacokinetic profile of ART and increase the in vivo efficacy of ART.…”
Section: Various Classes Of Nanomedicinesmentioning
confidence: 99%
“…Over the past few years, extensive research has been undertaken by many scholars on nanodynamic therapies aimed at combating tumors. This study spans the spectrum of innovative nanocarriers to optimize the TME and integrate various therapeutic strategies [26]. These efforts are based on catalyzing the production of reactive ROS within tumor cells and inducing tumor cell death.…”
Section: Introductionmentioning
confidence: 99%